Aplicación móvil de la red alumni para graduados de la ESPAM MFL - Marín Calderón, Francisco Joel (2022)
This curricular integration work consisted of developing the mobile application of the Red Alumni web platform; the main objective of this application is that graduates have at their fingertips all the benefits to which they have access on the web platform. For the structuring, planning and control of the development process of the application, the agile methodology Extreme Programming was used with its respective 4 phases which are: In the planning phase, the compilation of user stories and the definition of requirements and software requirements were carried out, all based on the IEEE 830 standard; in the design phase, a set of CRC cards, the application interfaces, as well as a glossary of terms that included the specification of the names of the methods and classes to be developed in the development phase, were elaborated; in the third phase, which includes coding, the source code of the application was developed using the Ionic framework and REST services linked to the Alumni Network, which were developed in C# language using the ASP. NET CORE FRAMEWORK. Finally, in the last phase corresponding to the tests, the correct functioning of the application was verified through unit and acceptance tests, which were approved by the group of stakeholders of the Computer Development Unit (UDC), resulting in the completion of the project and its delivery for its subsequent implementation.